Progress in English Language Teaching Through Continuous Professional Development—Teachers’ Self-Awareness, Perception, and Feedback - Vadivel, Balachandran; Namaziandost, Ehsan; Saeedian, Abdulbaset (Frontiers in Education, 2021)
This research aimed to investigate the various aspects of ESL teachers' professional development through Continuous Professional Development (CPD). Hence a study involving 83 ESL teachers from different socio-economic, multi-cultural, educational and disciplinary backgrounds was conducted to ascertain their attitudes, perceptions, and feedback on CPD. The sample population was random, and the data collection was through a questionnaire. The results showed that teachers take charge of their CPD, but for better outcomes, they need professional development through shared experience, reflective teaching, and have a sense of community among them to stay at par with the global standards of the education system. Through this research, the concept of CPD and its significance in teaching English are made available. This study also proposes higher achievement in education through teacher professional development programmes. Moreover, the analysis demonstrated that teachers are confident in what they do because of their positive belief in their own CPD. From the results, it was clear that every ESL teacher should take charge of their professional development to become better teachers and help students achieve their goals.